EVALUATING THE LEVEL OF POLLUTANTS FROM SPENT DRILLING FLUIDS IN AN OIL FIELD IN NIGER DELTA (Nigerian Journal of Technology, 2012)
The environmental pollution hazards due to the use of drilling fluids in the oil and gas sector were studied. Grab samples of spent drilling fluids (SDF), water and soil were collected from 7 locations in the oil field when the depth of the well was 3,658m, before the 3,962 m pay zone. Samples were analyzed to determine the concentrations of contaminants such as Barium (Ba), Cadmium (Cd), Chromium total (Cr), Copper (Cu), Iron III (Fe3+), Lead (Pb), Manganese (Mn), Vanadium (Vn) and Zinc (Zn) in the treated and untreated SDFs, water, soil, ash and sludge samples that might constitute environmental hazards, in accordance with the Department of Petroleum Resources and American Public Health Association’s guidelines and methods. The concentrations and the spatial distributions of the pollutants released to the environment were established through modeling with Ogata-Banks model equation and the material balance equations. The results of the test showed that these substances have levels above recommended limits in the environment. These contaminants which are deleterious, toxic and hazardous, have led to large-scale human health problems and environmental degradation in the sensitive wetlands of the Oil Field in the Niger Delta.